STRATEGI DIGITAL MARKETING DONDONG DALAM MENINGKATKAN BRAND AWARENESS MELALUI MEDIA SOSIAL PT HEAVENLY NUTRITION INDONESIA - Tri Wandini, Wardah; Hidayat, Aceng (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the digital marketing strategy of Dondong, a functional beverage brand by PT Heavenly Nutrition Indonesia, in building brand awareness through social media, particularly Instagram and TikTok @dondong_kedondong. While digital marketing strategies have been widely studied, empirical analysis of organic content strategies for functional beverage products targeting specific market segments remains limited. This study aims to: (1) analyze the workflow of the Digital marketing division; (2) describe the implementation of Dondong’s digital marketing strategy; and (3) evaluate its contribution to brand awareness growth. Using a qualitative descriptive case study approach, data were collected through active participation as a digital marketing intern, direct observation, in-depth interviews with the Brand manager and content staff directly involved in content production, and literature studies conducted during an internship from January to May 2026. This study applies the SOSTAC® Planning Framework (Smith, 1990) and Brand awareness Hierarchy (Aaker, 1991) as analytical frameworks. The results show that Dondong implemented an integrated digital marketing strategy encompassing organic content creation, collaboration with Key Opinion Leaders (KOL), and cross-platform content mirroring. During the internship period, organic content achieved an average of 200 likes and 500–2,000 views per post, while Instagram followers grew from 11,000 to 13,000. These findings suggest that a consistent, trend-adaptive organic content strategy contributes significantly to building brand awareness and advancing audiences from the unaware of brand stage toward top of mind awareness.